Social Participation of Diabetes and Ex-Leprosy Patients in the Netherlands and Patient Preference for Combined Self-Care Groups - de Vries, Henry J. C.; de Groot, Roos; van Brakel, Wim H. (Frontiers in Medicine, 2014)
Introduction: Earlier we showed that neuropathic complications limit social participation of ex-leprosy patients, even in a non-endemic leprosy setting like the Netherlands. Self-care groups for ex-leprosy patients can strengthen self-worth of participants, prevent further handicap, and enable the exchange of coping strategies. For non-endemic leprosy settings with a very low rate of leprosy patients a self-care group exclusively for (ex)leprosy patients is not likely to be feasible. A combined group with patients facing comparable morbidity would be more efficient than disease specific self-care groups. Here, we studied the comparability in social constraints of diabetic patients and ex-leprosy patients. Moreover, we investigated if combined self-care groups for ex-leprosy patients and diabetic patients would be desirable and acceptable for possible participants. Methods: Social participation was studied based on in-depth interviews and Participation Scale information collected from 41 diabetic patients and compared with the data of 31 ex-leprosy patients from a prior study. Moreover, we made an inventory of potential strengths and limitations and attitudes towards combined self-care groups for diabetic patients with neuropathy. Results: The following themes emerged among diabetic patients: disease confrontation, dependency, conflict with partner or relatives, feelings of inferiority, stigma, abandoning social activities, fear of the future, lack of information and hiding the disease. These themes were very similar to those voiced by the previously interviewed ex-leprosy patients. The latter more often mentioned stigma and disease ignorance among Dutch health care workers. Whereas ex-leprosy patients perceived stigma on multiple fronts, diabetic patients only mentioned feeling inferior. Diabetic patients experienced some form of participation restriction in 39% of the cases as opposed to 71% of the ex-leprosy patients. Diabetic patients did acknowledge the comparab